1988
DOI: 10.1111/j.1365-2044.1988.tb06624.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of beta‐adrenoceptor antagonism on the cardiovascular and catecholamine responses to tracheal intubation

Abstract: The catecholamine and cardiovascular responses to laryngoscopy and tracheal intubation were studied in 20 patients who u n r k m w ! elective gynaecological surgery and ivho were allocated randoml-v to receive either practolol I0 mg or saline in travewously

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…These stimulations trigger a wide range of sympathetic activations in the nervous system via the vagus and glossopharyngeus nerves. 13,14) Tracheal intubation is considered a stressful situation for a person undergoing general anaesthesia, which could be detrimental to patients with cardiac problems. Tachycardia and hypertension induced by TI decrease myocardial perfusion and increase oxygen consumption, both of which disrupt myocardial function.…”
Section: Discussionmentioning
confidence: 99%
“…These stimulations trigger a wide range of sympathetic activations in the nervous system via the vagus and glossopharyngeus nerves. 13,14) Tracheal intubation is considered a stressful situation for a person undergoing general anaesthesia, which could be detrimental to patients with cardiac problems. Tachycardia and hypertension induced by TI decrease myocardial perfusion and increase oxygen consumption, both of which disrupt myocardial function.…”
Section: Discussionmentioning
confidence: 99%
“…Beta-adrenoceptor blockade has proven effective in perioperative situations with increased sympathetic activity (8)(9)(10)(11)(12)(13), and attenuation of cardiovascular effects due to perioperative stimuli has been demonstrated (11)(12)(13)(14). However, the use of such drugs orally or intravenously before anaesthesia in patients not previously medicated with these drugs is still controversial (14-16).…”
mentioning
confidence: 99%
“…BIS decreased to 0 for 15 min, indicating that lidocaine and sevoflurance interact to decrease BIS. Laryngoscopy and tracheal intubation are thought to be the strongest noxious stimuli during the course of general anesthesia and are often associated with hemodynamic changes including tachycar-dia, hypertension and increases in the plasma concentration of catecholamines (Shribman et al, 1987;Achola et al, 1988). Nakatani et al(2005) investigated hemodynamic changes following induction of anesthesia with propofol during tracheal intubation with or without epidural anesthesia and found that epidural anesthesia did not produce profound hypotentension following induction of anesthesia and produced a reduction in the hemodynamic response to tracheal intubation during a target controlled infusion of propofol.…”
Section: Introductionmentioning
confidence: 99%